Relating dietary diversity and food variety scores to vegetable production and socio-economic status of women in rural Tanzania - Keding, G.B.; Msuya, JM; Maass, Brigitte L.; Krawinkel, M.B. (Springer, 2012)
The objective of the present study was to measure diversity in nutrition with dietary scores, and to assess their relationship to vegetable production and the socio-economic status of women in rural Tanzania. A dietary diversity score (DDS) and a food variety score (FVS) were created from data gathered with three semi-quantitative 24-h recalls performed during three non-consecutive seasons during 2006/2007. Data on vegetable production, selling and buying and socio-economic data was gathered with a semi-quantitative questionnaire. A total of 252 randomly selected women from three districts of north-eastern and central Tanzania participated. The median DDS of 6 and the mean FVS of 8.3 were low, suggesting an overall poor dietary quality, with about one third of participants having an alarmingly low DDS of only two to four food groups per day. These women consumed a very basic diet consisting mainly of cereals and vegetables. Differences among districts were pronounced while those among seasons were less distinct. The DDS and FVS were both significantly associated with ethnicity, occupation and status within the household of participants. As a more varied diet is not necessarily healthier, integration of both quantity and quality in the scores is proposed for future studies. This can be achieved, for example, by weighing food types according to their importance in the diet. As both scores are linked to the production, selling and buying of vegetables, the promotion of homestead food production may be a good way to improve dietary diversity.